Generating Function for Bernoulli Polynomials
Jump to navigation
Jump to search
Theorem
Let $\map {B_n} x$ denote the $n$th Bernoulli polynomial.
Then the generating function for $B_n$ is:
- $\ds \frac {t e^{t x} } {e^t - 1} = \sum_{k \mathop = 0}^\infty \frac {\map {B_k} x} {k!} t^k$
Proof
By definition of the generating function for Bernoulli numbers:
- $\ds \frac t {e^t - 1} = \sum_{k \mathop = 0}^\infty \frac {B_k} {k!} t^k$
By Power Series Expansion for Exponential Function:
- $\ds e^{t x} = \sum_{k \mathop = 0}^\infty \frac {x^k} {k!} t^k$
Thus:
- $\ds \frac {t e^{t x} } {e^t - 1} = \paren {\sum_{k \mathop = 0}^\infty \frac {B_k} {k!} t^k} \paren {\sum_{k \mathop = 0}^\infty \frac {x^k} {k!} t^k}$
Combining like powers of $t$ we obtain:
\(\ds \frac {t e^{t x} } {e^t - 1}\) | \(=\) | \(\ds \sum_{k \mathop = 0}^\infty t^k \sum_{m \mathop = 0}^k \frac {B_{k - m} } {\paren {k - m}!} \frac {x^m} {m!}\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{k \mathop = 0}^\infty \frac {t^k} {k!} \sum_{m \mathop = 0}^k \frac {k!} {\paren {k - m}! m!} B_{k - m} x^m\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{k \mathop = 0}^\infty \frac {t^k} {k!} \sum_{m \mathop = 0}^k \binom k m B_{k - m} x^m\) | Definition 1 of Binomial Coefficient | |||||||||||
\(\ds \) | \(=\) | \(\ds \sum_{k \mathop = 0}^\infty \frac {\map {B_k} x} {k!} t^k\) | Definition of Bernoulli Polynomial |
$\blacksquare$